IMPLEMENTASI METODE LAGRANGE UNTUK OPTIMASI PENYAKIT KANKER HATI - Tony Yulianto; Kuzairi Kuzairi; Riyatun Hasanah (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2016)
Modelling the math frequently encountered in everyday life , many things that can be modeled by mathematical modeling , one of which is the modeling of the disease. One of the diseases thoth can be modeled is liver cancer. Liver cancer is very much experienced by people, also cause a variety ranging from the spread of viruses and inveksi . Thus, in the mathematical modeling of the matter is that the modeling using Lagrange method not instant but through a few steps to get the optimal control of this modeling . Thus the optimization of liver cancer can be viewed from the optimal solution by applying the method of Lagrange. From the result of applying the method lagrange can be obtained results when tumor cells T = 0, immune cells I = 0, and addition of condition M = 0, that indicate a person is said to be normal N = 1.